2009
DOI: 10.1111/j.1095-8339.2009.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of after-ripening in promoting germination of arid zone seeds: a study on six Australian species

Abstract: The effects of after-ripening (storage under warm, dry conditions) on seed germination was examined in six plant species from the arid zone of Western Australia with the aim of improving germination and germination rate for rehabilitation objectives. Study species (Acanthocarpus preissii, Anthocercis littorea, Dioscorea hastifolia, Eremophila oldfieldii, Thryptomene baeckeacea and Zygophyllum fruticulosum) were selected based on diverse plant habits, seed types and requirements for rehabilitation. After-ripeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
0
33
0
1
Order By: Relevance
“…seeds were hydrated for 2 days, then redried for 28 days) significantly enhanced germination to 100% after the same storage time (Hoyle et al 2008 a ). In another study on arid zone species, Commander et al (2009 a ) assessed various combinations of relative humidity and storage temperatures, and found, for example, that dormancy loss of Dioscorea hastifolia seeds was significantly faster at 45°C than at 30°C. Such studies highlight the role that storage temperature and seed water content plays in DAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…seeds were hydrated for 2 days, then redried for 28 days) significantly enhanced germination to 100% after the same storage time (Hoyle et al 2008 a ). In another study on arid zone species, Commander et al (2009 a ) assessed various combinations of relative humidity and storage temperatures, and found, for example, that dormancy loss of Dioscorea hastifolia seeds was significantly faster at 45°C than at 30°C. Such studies highlight the role that storage temperature and seed water content plays in DAR.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies highlight the role that storage temperature and seed water content plays in DAR. Storing florets or seeds under differing environmental conditions, including exposure to treatments such as wet/dry cycling and/or chemical stimulants (Commander et al 2009 a ; Hidayati et al ), may assist in further refining dormancy break of Triodia , particularly those species that have not responded to the DAR conditions imposed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, endospermic seeds tended to be shorter lived than non‐endospermic seeds and species originating in hot, dry climates were longer lived than those from cool, wet climates. Commander et al. (2009), among others, have demonstrated that many species from desert environments are dormant at maturity and may require after ripening to increase germination percentages.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples include the use of mechanical or chemical abrasion, wet or dry heat, dry after‐ripening, warm and cold stratification, and the use of chemical stimulants (e.g. gibberellic acid, karrikinolide, and ethylene) (Hargurdeep et al ; Morris ; Bonner & Karrfalt ; Commander et al 2009 a , 2009 b ; Turner et al ; Kildisheva et al ; Baskin & Baskin ; Erickson et al 2016 a ). A number of dormancy alleviation techniques have been successfully applied in the context of large‐scale restoration (Rokich et al ; Rokich & Dixon ; Erickson et al 2016 a ).…”
Section: Introduction To Drylands and Overview Of The Special Issuementioning
confidence: 99%